Perbandingan Instrumen Pembiayaan Bank Mega Syariah: Mudharabah, Musyarakah, Ijarah, Istisna, dan Murabahah - Catherine Catherine; Eileen Mirabelle; Gandi Gandi; Novita Novita; Tryen Lux Shandova Manalu; Vian Ervina (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Bank Mega Syariah is one of the leading Islamic financial institutions in Indonesia. The bank was established with the aim of providing banking services in accordance with sharia principles in Islam. The main Islamic banking concepts, namely Mudharabah, Musyarakah, Ijarah, Istishna, and Murabahah, in the context of Bank Mega Syariah. This study analyzes the proportion of each instrument to the bank's total financing and classifies the instruments based on the social needs pyramid of the higher ethical objective (maqashid sharia), including classification as pseudo-Islamic, sharia compliance, or sharia-based.